2022
DOI: 10.3389/fmicb.2022.973996
|View full text |Cite
|
Sign up to set email alerts
|

A novel detection method for the pathogenic Aeromonas hydrophila expressing aerA gene and/or hlyA gene based on dualplex RAA and CRISPR/Cas12a

Abstract: Aeromonas hydrophila is an emerging waterborne and foodborne pathogen with pathogenicity to humans and warm water fishes, which severely threatens human health, food safety and aquaculture. A novel method for the rapid, accurate, and sensitive detection of pathogenic A. hydrophila is still needed to reduce the impact on human health and aquaculture. In this work, we developed a rapid, accurate, sensitive, and visual detection method (dRAA-CRISPR/Cas12a), without elaborate instruments, integrating the dualplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Meanwhile, the activity of the F1/R1-CR3 combination was also verified using RAA-CRISPR/Cas12a-LFS method (Figure 2(d)). The validity of the F1/R1-CR3 combination was further confirmed in the specificity test of two RAA-CRISPR/Cas12a-based methods, which shows that only six C. perfringens strains could be detected using the established methods, RAA-CRISPR/Cas12a-FL (Figure 5 Previously, RAA assay coupled with CRISPR/Cas12a system has been established for pathogen detection and showed high sensitivity [28,29]. In this study, these results demonstrated that RAA-CRISPR-Cas12a-FL and RAA-CRISPR/ Cas12a-LFS methods based on fluorescence signal and colorimetric signal detected the C. perfringens genomic DNA at a sensitivity level of 2 copies/reaction (Figure 4(a)) and 20 copies/reaction (Figure 4(b)), respectively.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Meanwhile, the activity of the F1/R1-CR3 combination was also verified using RAA-CRISPR/Cas12a-LFS method (Figure 2(d)). The validity of the F1/R1-CR3 combination was further confirmed in the specificity test of two RAA-CRISPR/Cas12a-based methods, which shows that only six C. perfringens strains could be detected using the established methods, RAA-CRISPR/Cas12a-FL (Figure 5 Previously, RAA assay coupled with CRISPR/Cas12a system has been established for pathogen detection and showed high sensitivity [28,29]. In this study, these results demonstrated that RAA-CRISPR-Cas12a-FL and RAA-CRISPR/ Cas12a-LFS methods based on fluorescence signal and colorimetric signal detected the C. perfringens genomic DNA at a sensitivity level of 2 copies/reaction (Figure 4(a)) and 20 copies/reaction (Figure 4(b)), respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Cas12a (Cpf1), an RNA-guided DNA-targeting enzyme, recognizes DNA sequence as an activator and then cleaves nonspecific singlestrand DNA reporter (termed collateral cleavage) [23]. Based on this property, CRISPR/Cas12a-based nucleic acid detection system combined with RAA or LAMP has been successfully applied to detect a variety of pathogens, such as SARS-CoV-2 [27], human papillomavirus [23], Vibrio vulnificus [28], Aeromonas hydrophila [29], Escherichia coli O157:H7 [30], and Streptococcus aureus [30].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity and sensitivity of RAA-CRISPR/Cas12a-based detection methods are mainly influenced by the choice of the RAA primer pair and crRNA sequence. 41,42 To develop an RAA-CRISPR/Cas12a-based NiV detection method with high specificity and sensitivity, we designed seven RAA primer pairs and five crRNAs according to the principle mentioned in Materials and Methods, and then screened the optimal combination of RAA primer pair and crRNA from those 10 combinations shown in Fig. 2A.…”
Section: Resultsmentioning
confidence: 99%